2020
DOI: 10.4018/ijdst.2020010104
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Information Architecture on the Usability of a University Website

Abstract: A well-planned information architecture (IA) of a website can enhance the end users' efficiency, learnability, controllability and intention to revisit the site. Its significance is even more in the context of academic websites where the generation, management, and distribution of information are among the major activities. However, it remains a neglected issue as designers of academic websites have overlooked the important aspect of ‘intuitive user navigation' and focused primarily on its ‘look and feel.' Thu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
1
0
1
Order By: Relevance
“…In particular, they were pleased with the ‘content and navigation (ease of use)’ features of the websites but were discontent with the ‘design of the websites’. Singla and Aggarwal (2020) found that design and navigation of academic websites are not given much importance which affected the websites adversely. Mentes and Turan (2012) had studied the usability of Namik Kemal University’s website with the use of WAMMI scale and it was found that website usability is positively associated with attractiveness, helpfulness, efficiency and learnability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In particular, they were pleased with the ‘content and navigation (ease of use)’ features of the websites but were discontent with the ‘design of the websites’. Singla and Aggarwal (2020) found that design and navigation of academic websites are not given much importance which affected the websites adversely. Mentes and Turan (2012) had studied the usability of Namik Kemal University’s website with the use of WAMMI scale and it was found that website usability is positively associated with attractiveness, helpfulness, efficiency and learnability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…ingreso y egreso, las competencias documentadas por ciclos, el plan de estudios, el personal académico, tecnologías utilizadas o que se verán en el transcurso de la carrera y su mapa curricular (Universidad-Politécnica-de-Victoria, 2023). El diseño del mapa curricular es uno de los aspectos que hace que se vea muy útil, es por esto que al desarrollar un currículo se necesita equilibrar las habilidades de producción y codificación, así como el uso de herramientas para su desarrollo en conjunto con el diseño visual (Kuo et al, 2021;Singla & Aggarwal, 2020).…”
unclassified